The Role of Corporate Social Responsibility (CSR) on Natural Disaster Risk Reduction in Indonesia - Ratna Ningsih Ningsih; Pompong B. Setiadi (Yayasan Ilomata, 2023)
Indonesia has geographic, demographic, and sociological conditions that cause Indonesia to have a relatively high percentage and risk of natural disasters. The Ministry of Finance noted that every year losses due to natural disasters reach Rp. 20 trillion. In addition, the impact of natural disasters on society is also negatively affected by economic conditions. This condition creates a real urgency for the role of all levels of society in making social contracts to help each other during emergencies. The Corporate Social Responsibility (CSR) program is a form of corporate responsibility in paying attention to the welfare of the community as a form of corporate social and economic responsibility in carrying out its operations. Currently, the awareness of business entities in preventing natural disasters is still not optimal and the role of CSR is still limited to charity. This journal will review the role of companies through Corporate Social Responsibility (CRR) in reducing the risk of natural disasters in Indonesia.